Medicinal Chemistry of Neglected Tropical Diseases Advances in the Design and Synthesis of Antimicrobial Agents. - Jayaprakash, Venkatesan; Castagnolo, Daniele; Ozkay, Yusuf (Milton : CRC Press LLC, 2019)
Medicinal Chemistry of Neglected and Tropical Diseases: Advances in the Design and Synthesis of Antimicrobial Agents consolidates and describes modern drug discovery and development approaches currently employed to identify effective chemotherapeutic agents for the treatment of Neglected Tropical Diseases (NTDs) from a medicinal chemistry perspective. Chapters are designed to cater to the needs of medicinal chemists who work with chemotherapeutic developments for NTDs, as well as serve as a guide to budding medicinal chemists who wish to work in this area. It will introduce rational drug design approaches adopted in designing chemotherapeutics and validated targets available for the purpose.
13: New Biological Targets for the Treatment of Leishmaniasis14: Curcumin and Neglected Infectious Diseases; 15: An Overview of Helminthiasis: Current State and Future Directions; Index; Color Plate Section
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Tropical medicine; MEDICAL / Infectious Diseases; MEDICAL / Pharmacy; SCIENCE / Chemistry / General